2018
DOI: 10.1111/jep.12918
|View full text |Cite
|
Sign up to set email alerts
|

Lowered quality of life in mood disorders is associated with increased neuro‐oxidative stress and basal thyroid‐stimulating hormone levels and use of anticonvulsant mood stabilizers

Abstract: These data show that lowered HRQoL in major affective disorders could at least in part result from the effects of lipid peroxidation, protein oxidation, lowered antioxidant enzyme activities, and higher levels of TSH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 69 publications
3
19
0
Order By: Relevance
“…This might be due to their ability to maintain the balance of the intestinal microbiota, regulate the immunomodulatory responses as well as suppression of the potential pathogens, and the inhibition of carcinogenesis [ 12 , 16 , 17 ]. Since elevated inflammation and oxidative stress are associated with impairment of quality of life [ [20] , [21] , [22] , [23] , [24] ], thus, using synbiotics might be promising in improving the quality of life in patients with BCRL.…”
Section: Introductionmentioning
confidence: 99%
“…This might be due to their ability to maintain the balance of the intestinal microbiota, regulate the immunomodulatory responses as well as suppression of the potential pathogens, and the inhibition of carcinogenesis [ 12 , 16 , 17 ]. Since elevated inflammation and oxidative stress are associated with impairment of quality of life [ [20] , [21] , [22] , [23] , [24] ], thus, using synbiotics might be promising in improving the quality of life in patients with BCRL.…”
Section: Introductionmentioning
confidence: 99%
“…In the current study, we found that the cumulative effects of multiple ELTs, which appear to drive most outcome variables, are in fact mediated by the recurrence-staging index. Such findings may be explained by the knowledge that recurrent episodes and especially reoccurring suicidal attempts and suicidal ideation may affect work productivity and functions, thereby contributing to lower socio-economic status [33,[98][99][100]. Moreover, ELTs and recurrent patterns and suicidal behaviors may affect the severity of illness, which in turn is accompanied by decreased HR-QoL [33,101].…”
Section: --↓mentioning
confidence: 99%
“…Additionally, the outcome variables measured here were strongly related with lipid-associated antioxidant defenses, including income, CGI, HR-QoL and disabilities. Recently, we reported that lowered HR-QoL and its subdomains in affective disorders are associated with increased levels of malondialdehyde, advanced oxidation protein products and lowered CMPAase PON1 activity [33]. Finally, there is now some evidence that increased neuro-oxidative stress and neuro-immune pathways may affect neurocognitive functions in affective disorders [108].…”
Section: --↓mentioning
confidence: 99%
See 1 more Smart Citation
“…Is it possible to establish a direct link for translation from neuroscience to public health outcomes (such as, for example, quality of life), and what are the appropriate study designs to achieve this? A remarkable contribution to the Special Section from Nunes and Maes addresses such a question directly, connecting quality of life in psychiatric patients with immediate clinical and neurobiological markers of disease and producing diagnostic categories by machine learning experiments that target specific constellations of clinico‐biological markers, known also as “biological signatures” of disease . Research of this type surely opens an avenue for debate on the possibility of integrating all those levels and sources of enquiry and yet avoids the trap of ontological reductionism.…”
Section: Translating the Findings Of Neuroscience Into Clinical Medicmentioning
confidence: 99%